ChemInform Abstract: N‐Bridged Dimers of Tetrapyrroles Complexed by Transition Metals: Syntheses, Characterization Methods, and Uses as Oxidation Catalysts. Issue 28 (July 2015) - Isci, Umit; Dumoulin, Fabienne; Sorokin, Alexander B.; Ahsen, Vefa
Abstract Review: 86 refs.